The impact of delirium on clinical outcomes in multi-center thai surgical intensive care units: A prospective cohort study - Pipanmekaporn T. (2017)
© 2016, Medical Association of Thailand. All rights reserved. Objective: Delirium in intensive care units (ICU) increases risks in prolonged mechanical ventilation, hospitalization, and mortality rate. The purpose of this study is to determine if delirium in the surgical intensive care units (SICU) is an independent predictor of clinical outcomes during hospitalization. Material and Method: A multi-center, prospective cohort study was conducted between April 2011 and January 2013. All patients who were admitted to nine university-based SICU were enrolled. Delirium was diagnosed by using the Intensive Care Delirium Screening Checklists. The clinical outcomes of study included length of mechanical ventilation, length of hospital stay, ICU and 28 day mortality. Cox proportional hazard regression model was used to assess the effects of delirium on ICU and 28 day mortality. Results: A total of 4,652 patients were included. One hundred and sixty-three patients were diagnosed delirium (3.5%, 163 of 4,652). Patients who experienced delirium during ICU admission were significantly older (65.0+15.8 years versus 61.6+17.3 years, p = 0.013), had higher American Society of Anesthesiologists physical status (24.3% versus 12.2%, p < 0.001), higher Acute Physiology and Chronic Health Evaluation II score (16 (12-23) versus 10 (7-15), p < 0.001), and higher Sequential Organ Failure Assessment score (5 (2-8) versus 2 (1-5), p < 0.001) compared to non-delirium. Delirious patients also had higher ventilator days (7 (4-17) versus 2 (1-4), p < 0.001, longer length of hospital stay (22 (14-34) versus 15 (9-26), p < 0.001) and higher ICU mortality (24% versus 9%, p < 0.001), and 28-day mortality (28% versus 13%, p < 0.001). Patients who developed delirium in the intensive care unit were associated with increased 28-day mortality (adjusted HR = 2.47, 95% CI: 1.13-5.41, p = 0.023). Conclusion: Delirium in an ICU was a major predictor of hospital mortality after adjusted for relevant covariates. Routine monitoring of delirium, ea rly detection, and implementation of preventive strategy are recommended.